Engineered CAF-cancer cell hybrid membrane biomimetic dual-targeted integrated platform for multi-dimensional treatment of ovarian cancer - Yuwei Yao; Jiarui Zhang; Kexin Huang; Yingying Peng; Shuangshuang Cheng; Shuangge Liu; Ting Zhou; Jinhua Chen; Haojia Li; Yingchao Zhao; Hongbo Wang (Journal of Nanobiotechnology)
Abstract Background The efficacy of current therapies for ovarian cancer is limited due to the multilevel and complex tumor microenvironment (TME), which induces drug resistance and tumor progression in a single treatment regimen. Additionally, poor targeting and insufficient tissue penetration are important constraints in ovarian cancer treatment. Result We constructed PH20-overexpressing cancer-associated fibroblast (CAF)-cancer hybrid-cell membrane vesicles (PH20/CCM) for the dual-targeted delivery of carboplatin (CBP) and siRNA targeting p65 (sip65) loaded on the poly (dimethyl diallyl ammonium chloride) (PDDA)-modified MXene (PMXene), named PMXene@CBP-sip65 (PMCS). The nanoparticle PH20/CCM@PMCS could penetrate the extracellular matrix of tumor tissues and target both cancer cells and CAFs. After tumor cell internalization, these nanoparticles significantly inhibited cancer cell proliferation, generated reactive oxygen species, induced endoplasmic reticulum stress, and triggered immunogenic cell death. After CAF internalization, they inhibited pro-tumor factor release and activated immune effects, promoting immune system infiltration. In an experiment with ID8 homograft-carrying mice, PH20/CCM@PMCS significantly improved tumor inhibition and enhanced immune infiltration in tumor tissues. Conclusion These new therapeutic nanoparticles can simultaneously target tumor cells, CAFs, immune cells, and the extracellular matrix, thereby increasing treatment sensitivity and improving the TME. Therefore, these TME-regulating nanoparticles, combining specificity, efficiency, and effectiveness, provide new insights into ovarian cancer treatment. Graphical Abstract